PENERAPAN PEMBELAJARAN KIMIA BERBASIS CHEMO-ENTREPRENEURSHIP PADA MATERI LARUTAN PENYANGGA KELAS XI SISWA SMA CITRA KASIH MANADO - Runtuwene, Christiana Paula; Rumampuk, Rymond; Tengker, Soenandar; Kaeng, Meilanie; Pongoh, Emma (Chemistry Department, Universitas Negeri Manado, 2025)
This study aims to determine the effect of applying Chemo-Entrepreneurship (CEP)-based chemistry learning on students' engagement and learning outcomes in the buffer solution material for Grade XI students at SMA Citra Kasih Manado. This research employed a Classroom Action Research (CAR) method conducted in two cycles, each consisting of planning, implementation, observation, and reflection stages. The research instruments included student activity observation sheets and learning outcome tests. The results showed that the application of CEP-based learning significantly increased students' engagement and learning outcomes. The average learning activity score increased from 42.5% (categorized as low) in the first cycle to 90% (categorized as very good) in the second cycle. The average learning outcome score also rose from 56 in the first cycle to 89 in the second cycle, achieving a 100% mastery level. The implementation of Chemo-Entrepreneurship through a research-based learning model proved effective in enhancing student engagement, creativity, and understanding of buffer solution concepts. Therefore, this approach is recommended for use in other chemistry learning topics to foster entrepreneurial potential and 21st-century skills among students.